Characterisation of the chocolate aroma in roast jackfruit seeds. (30th August 2021) - Spada, Fernanda Papa; Balagiannis, Dimitrios P.; Purgatto, Eduardo; do Alencar, Severino Matias; Canniatti-Brazaca, Solange Guidolin; Parker, Jane K.
Highlight: Jackfruit seeds were processed and roasted to generate chocolate aroma. Aroma was compared in seeds that were dried, acidified or fermented prior to roasting. Typical cocoa aroma compounds were produced in all cases. 40 different pyrazines were identified and confirmed with bespoke process reactions. Fermented jackfruit seeds produced the most cocoa-like aroma. Abstract: The seeds of the jackfruit (Artocarpus heterophyllus Lam.) are an abundant waste-stream in Brazil and a potential source of chocolate aroma. The aim of the study was to characterise the aroma compounds in flours prepared from the roasted jackfruit seeds and compare them with a typical Brazilian cocoa powder. Jackfruits seeds were either left untreated, acidified or fermented before drying and roasting. The volatiles were extracted using solid phase micro extraction or solid phase extraction and analysed by gas chromatography mass spectrometry. The most odour-active volatiles were identified by GC-Olfactometry. Most of the compounds known to be odour-active character impact compounds in cocoa products were also found in the jackfruit seed flours, however, the jackfruit seeds produced many additional pyrazines, some of which were responsible for the characteristic earthy "roasted jackfruit seed" aroma. The fermented sample had the most similar aroma profile to cocoa powder.